Kebijakan Pemerintah Kota Cirebon di Bidang Ketertiban Umum Dalam Menerapkan PPKM Darurat - Sony Suharto; iis Krisnandar; Sanusi Sanusi (Publikasi Indonesia, 2022)
The title of this research is Cirebon City Government Policy In The Field Of Public Order In Implementing Emergency PPKM. The research method used by the researcher is using the constructivism paradigm and the type of qualitative research with a socio-legal research approach. The results of the study from this research are the policies carried out by the Cirebon City government in implementing Emergency PPKM have been carried out with the help of related devices or agencies, but because they were carried out suddenly so that the policies implemented could not work well. The government hopes that with this policy there will be no crowds, which is to avoid the spread of Covid-19 which will be accepted by the community if it is not prevented, but the facts on the ground that occur are the lack of information received by the public so that people do not know the requirements. What conditions are needed to be able to do activities in Cirebon City, so that what happens is a long traffic jam on the border of Cirebon City, which in the end results in crowds in public spaces. In connection with the fulfillment of the rights of the people of Cirebon City who are affected by the Emergency PPKM, assistance has been distributed from the government, and it is hoped that in the future the assistance distributed can be received effectively and efficiently.